Gymnastics Asthma Affects the Respiratory Pattern of Asthma Sufferers - Setiawan, Arif Helmi; Zahroh, Chilyatiz; Eviana, Lilik (International Journal of Psychosocial Rehabilitation, 2020)
Asthmatic sufferers have a respiratory abnormalation causing shortness of breath. So that asthma sufferers can have difficulty in breathing. To improve the respiratory pattern in asthma sufferers, it is necessary to prepare asthma gymnastics in daily life. Purpose of this research to know the influence of asthma to breathing patterns in asthma sufferers in Posyandu Reksowerdo III Wonokromo Surabaya. The design of this research was Quasy-Experiment (pre posttest control design.) Population of 50 people and sample of 46 respondents with simple random sampling technique . The independent variable of this study was asthma gymnastics and the dependent variable was the breathing pattern. The research instrument used questionnaires and observation sheets. Data analysis using test Wilcoxon and Mann Whitney with significance value α = 0,05. The results showed that after the statistical tests Wilcoxon and Mann Whitney obtained ρ = 0.000 <α = 0.05 indicates there is influence between asthma and asthma exercises on asthma patients in Posyandu Reksowerdo III Wonokromo Surabaya. There are differences in respiratory pattern in patients with intervention group asthma before and after asthma gymnastic performed at Posyandu Reksowerdo III Wonokromo Surabaya. Therefore, it is expected that people can apply asthma gymnastics in daily life in order to improve respiratory pattern and improve asthma control.